2020
DOI: 10.23887/ijssb.v4i4.29017
|View full text |Cite
|
Sign up to set email alerts
|

An Implication of Destination Attractiveness, Environmental Sensitivity, and Satisfaction with Interpretive Service on Place Attachment and Environmental Responsible Behavior

Abstract: This study examines the effect of destination attractiveness, environmental sensitivity, and satisfaction with interpretive services on place attachment. This study also aims to identify the effect of place attachment on environmentally responsible behaviour. This study was using a questionnaire as a data collection method. This study's total sample was 400 respondents—however, the number of questionnaires that can be processed as 398. The data were processed using PLS-SEM (Partial Least Square). The result wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(38 reference statements)
0
4
1
Order By: Relevance
“…Surprisingly, the environmental sensitivity of volunteer scuba divers exhibited no significant effect on destination social responsibility or environmentally responsible behaviors, which is different from the findings of related studies [12,44]. However, the results of this study do not mean a lack of empathy and concern for the marine environment among volunteer scuba divers, or a lack of marine destination responsibility and environmentally responsible behaviors; instead, other factors contribute to this causal outcome.…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, the environmental sensitivity of volunteer scuba divers exhibited no significant effect on destination social responsibility or environmentally responsible behaviors, which is different from the findings of related studies [12,44]. However, the results of this study do not mean a lack of empathy and concern for the marine environment among volunteer scuba divers, or a lack of marine destination responsibility and environmentally responsible behaviors; instead, other factors contribute to this causal outcome.…”
Section: Discussioncontrasting
confidence: 99%
“…Environmental sensitivity is a set of affective attributes that may result in an individual perceiving environmental concern empathetically ( Perterson, 1982 ). Environmental sensitivity is a construct that affects place attachments and environmental attitudes toward environmentally friendly behavior ( Saputra and Putra, 2020 ). Even though it promotes environmental stewardship behaviors, environmental sensitivity has received relatively less attention from researchers ( Ananda and Hampf, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, more attention is necessary to explore environmental sensitivity to increase pro-environmental behaviors (Metzger and Mcewen, 1999). A previous study (Saputra and Putra, 2020) showed that environmental sensitivity had a significant and positive effect on place attachment. Further, environmental sensitivity and place attachment both positively influenced environmentally responsible behavior.…”
Section: Moderator: Environmental Sensitivitymentioning
confidence: 99%
“…However, it can be very useful for practitioners to measure the place attachment of the country's nationals at a dark-heritage tourist destination. There are a plethora of studies that have measured the relationship between place attachment and tourists' satisfaction in the dark tourism context (Prayag et al, 2018;Saputra and Putra, 2020). However, very few have paid attention to the very crucial aspect of tourist loyalty (Wang et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…There are a plethora of studies that have measured the relationship between place attachment and tourists' satisfaction in the dark tourism context (Prayag et al. , 2018; Saputra and Putra, 2020). However, very few have paid attention to the very crucial aspect of tourist loyalty (Wang et al.…”
Section: Introductionmentioning
confidence: 99%